2011
DOI: 10.1111/j.1365-3040.2011.02422.x
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of acid phosphatase activity in ectomycorrhizal tissues depends on soil fertility and morphotype, and relates to host plant phosphorus uptake

Abstract: Acid phosphatase (ACP) enzymes are involved in the mobilization of soil phosphorus (P) and polyphosphate accumulated in the fungal tissues of ectomycorrhizal roots, thereby influencing the amounts of P that are stored in the fungus and transferred to the host plant. This study evaluated the effects of ectomycorrhizal morphotype and soil fertility on ACP activity in the extraradical mycelium (ACPmyc), the mantle (ACPmantle) and the Hartig net region (ACPHartig) of ectomycorrhizal Nothofagus obliqua seedlings. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The exploration of large soil volumes by the ERM in which orthophosphate (Pi) is scavenged and delivered to plant cortical cells, bypassing the plant pathway for P uptake [66,67] (Figure 4);  The small hyphal diameter that allows the fungus to penetrate into small soil cores in search for P, and higher P influx rates per surface unit [66,68];  The capability of mycorrhizal fungi to store P in form of polyphosphates, which allows the fungus to keep the internal Pi concentration relatively low, and allows an efficient transfer of P from the ERM to the IRM [69]; and  The production and secretion of acid phosphatases and organic acids that facilitate the release of P from organic complexes [70,71].…”
mentioning
confidence: 99%
“…The exploration of large soil volumes by the ERM in which orthophosphate (Pi) is scavenged and delivered to plant cortical cells, bypassing the plant pathway for P uptake [66,67] (Figure 4);  The small hyphal diameter that allows the fungus to penetrate into small soil cores in search for P, and higher P influx rates per surface unit [66,68];  The capability of mycorrhizal fungi to store P in form of polyphosphates, which allows the fungus to keep the internal Pi concentration relatively low, and allows an efficient transfer of P from the ERM to the IRM [69]; and  The production and secretion of acid phosphatases and organic acids that facilitate the release of P from organic complexes [70,71].…”
mentioning
confidence: 99%
“…Exploration type of the EMF assemblage is likely an important factor influencing P acquisition. There are significant differences in the mantles and exploration types of EMF fungi [55], and EMF taxa vary in the amount of mantle as a proportion of total structure [56]. A given EMF species may have lower enzyme efficiency or infection frequency across root tips, but a more extensive hyphal system that would facilitate access to P from greater distances could result in greater overall P uptake.…”
Section: Patterns Of Emf Enzyme Activitiesmentioning
confidence: 99%
“…For this purpose, the commercially available kits are applicable (Johnson & Spence 2010). Alvarez et al (2004Alvarez et al ( , 2012 used commercial kit ELF® 97 for analyses of surface-bound phosphatase activity. ELF® 97 contains a soluble ELF substrate, which forms an intense yellow-green-fluorescent alcohol precipitate at the site of phosphatase activity.…”
Section: Zaključkimentioning
confidence: 99%
“…The correlation between the acid phosphatase, and the temperature and humidity were also observed by Criquet et al (2004) in the leaf litter. Alvarez et al (2012) studied the influence of morphotypes (Paxillus involutus, Pisolithus tinctorius, Cenococcum geophilum, Descolea Antartica) and soil fertility on acid phosphatase activity. They found that spatial distribution of acid phosphatase in mycorrhizal mycelium is affected by mycorrhizal morphotype (extraradical mycelium, mycorrhizal mantle and Hartig net), while soil fertility had a significant effect on the enzymatic activity in the extraradical mycelium and Hartig net.…”
Section: Zaključkimentioning
confidence: 99%
See 1 more Smart Citation